2014
DOI: 10.1155/2014/434272
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Oil Reinjection without Macular Buckling for Treatment of Recurrent Myopic Macular Hole Retinal Detachment after Silicone Oil Removal

Abstract: Purpose. To evaluate the efficacy of silicone oil (S.O) reinjection without macular buckling for treatment of recurrent myopic macular hole retinal detachment (MHRD) after silicone oil removal. Methods. A retrospective consecutive interventional study from medical reports on cases of myopic MHRD. Fifty-three eyes of 51 patients underwent silicone oil removal after successful repair of MHRD were reviewed. The main outcomes were the retinal status after silicone oil removal and management of recurrent cases. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…The authors did not comment on the type of macular hole closure. Ghoraba et al 20 reported retinal re-attachment and macular hole closure in 88.7% of eyes. They had 23 months mean follow-up period after silicone oil removal.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The authors did not comment on the type of macular hole closure. Ghoraba et al 20 reported retinal re-attachment and macular hole closure in 88.7% of eyes. They had 23 months mean follow-up period after silicone oil removal.…”
Section: Discussionmentioning
confidence: 98%
“…The authors did not comment on the type of macular hole closure. Ghoraba et al 20 reported retinal re- For personal use only. primary retinal re-attachment and to maintain long-term success after silicone oil removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as ophthalmology is concerned, silicone oil tamponades have already been evaluated as beneficial treatment modality for endophthalmitis 4 and retinal detachment. [5][6][7] In this context, no toxic effect to retinal cells has been detected for low-and high-viscosity silicone oils. 8 The first silicone oil vitrectomy took place over 50 years ago and ever since this material has been retained as suitable vitreous substitute due to its optical transparency and chemical inertness (for review, see Refs [9 and 10]).…”
Section: Introductionmentioning
confidence: 91%
“…Even an antiviral and antimicrobial effect has been unraveled. As far as ophthalmology is concerned, silicone oil tamponades have already been evaluated as beneficial treatment modality for endophthalmitis and retinal detachment . In this context, no toxic effect to retinal cells has been detected for low‐ and high‐viscosity silicone oils .…”
Section: Introductionmentioning
confidence: 99%